Pediatric sickle cell disease and obstructive sleep apnea: A cross-sectional study in a tertiary pediatric center in Saudi Arabia - Wadha Alotaibi; Safa Eltahir; Mohmmed Rayis; Khalid Al-Mobaireek; Ayah Alsarheed; Gawahir Mukhtar; Jumageldi Jumayev; Suhail Al-Saleh (Wolters Kluwer Medknow Publications, 2018)
Objective: The aim of the study was to evaluate snoring and obstructive sleep apnea (OSA) in Saudi children with sickle cell disease (SCD). Materials and Methods: This cross-sectional study was conducted among children with SCD attending a hematology clinic were recruited. Demographics, clinical data, and sleep questionnaires were collected and overnight polysomnographies performed. Results: Seventy children (31 of whom were females) with SCD were included in the study. Their median (interquartile) age was 9 (6.5, 11) years and their body mass index z-score was −1.2 (−2.0, −0.4). Seventy-four percent of SCD patients snored and 32 (46%) had evidence of OSA (obstructive apnea-hypopnea index [OAHI] ≥2 events per hour of sleep), 13 of whom had moderate OSA (OAHI ≥5 and <10 events per hour of sleep) and 10 had severe OSA (OAHI ≥10 events per hour of sleep). Conclusion: Snoring and the proportion of OSA were high in children with SCD. This underlines the importance of screening for OSA in all children with SCD.